The emerging global threat landscape - Rohan Gunaratna (2013)
The global threat landscape this year will be shaped by the impending withdrawal of US-led coalition forces from Afghanistan. Jihadists will seek to extend their activities in Central and West Asia as well as North Africa, compounded by the uprisings in the Middle East. Al Qaeda associates will continue to pose a real threat to the US in the region and beyond.